Bio-Economics of Different Dry Direct Seeded Winter Rice Based Intercropping Systems Under Varying Fertilizer Management (Bangladesh Agronomy Journal, 2020)
The experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during February to June 2017 to study the feasibility of different direct seeded rice based intercropping systems under varying fertilizer management. The experiment was conducted in afactorialrandomized complete block design with three replications. Four leafy vegetables viz., gimakalmi, Indian spinach, red amaranth andjute were intercropped with dry direct seeded boro rice (cv. BRRI dhan28) following three fertilizer dose such as 100, 75 and 125% of recommended fertilizer, and sole rice was also maintained as control. Rice yield was the highest (3.87t ha-1) in sole cropping, and intercroppingresulted insignificant rice yield reduction. Although inintercropping rice yielddecreased, but increased both gross margin and benefit cost ratio (BCR) as compared to rice sole cropping. Among the vegetables, gimakalmi performed the best followed by red amaranth in terms of yield and 125% recommended fertilizer was the best fertilizer dose. Gimakalmi intercropped with rice following 125% recommended fertilizer showed the highest gross return and BCR (2.53). Therefore, vegetables like gimakalmi and red amaranth couldbe recommended as intercrop with dry direct seeded winter rice with 125% recommended fertilizer for better productivity and higher economicreturn.Bangladesh Agron. J. 2019, 22(2): 103-112